Age- and sex-related changes in vibrotactile sensitivity of hand and face in neurotypical adults. (March 2015) - Venkatesan, Lalit; Barlow, Steven M.; Kieweg, Douglas
Abstract Sensory perception decreases with age, and is altered as a function of sex. Very little is known about the age- and sex-related changes in vibrotactile detection thresholds (VDTs) of the face relative to the glabrous hand. This study utilized a single-interval up/down (SIUD) adaptive procedure to estimate the VDT for mechanical stimuli presented at 5, 10, 50, 150, 250, and 300 Hz at two sites on the face, including the right non-glabrous surface of the oral angle and the right lower lip vermilion; and on the hand on the glabrous surface of the distal phalanx of the right dominant index finger. Eighteen right-handed healthy younger adults and 18 right-handed healthy older adults participated in this study. VDTs were significantly different between the three stimulus sites (p < 0.0001), and dependent on stimulus frequency (p < 0.0001) and the sex of the participants (p < 0.005). VDTs were significantly higher for older adults when compared to younger adults for the finger stimulation condition (p < 0.05). There were significant differences (p < 0.05) in cheek and lower lip VDTs between male and female subjects. Difference in the VDTs between the three stimulation sites is presumed to reflect the unique typing and distribution of mechanoreceptors in the face and hand. Age-related differences in finger skin sensitivity are likely due to changes in the physical structure of skin, changes in the number and morphology of the mechanoreceptors, differences in the functional use of the hand, and its central representation. Sex-related differences in the VDTs may be due to the differences in tissue conformation and thickness, mechanoreceptor densities, skin hydration, or temperature characteristics.